2015
DOI: 10.1038/ncomms9909
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic consequences of a single G-quadruplex demonstrate mitotic inheritance of DNA replication fork barriers

Abstract: Faithful DNA replication is vital to prevent disease-causing mutations, chromosomal aberrations and malignant transformation. Accuracy, however, conflicts with pace and flexibility, and cells rely on specialized polymerases and helicases to ensure effective and timely replication of genomes that contain DNA lesions or secondary structures. If and how cells can tolerate a permanent barrier to replication is, however, unknown. Here, we show that a single unresolved G-quadruplexed DNA structure can persist throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 29 publications
7
96
0
1
Order By: Relevance
“…We speculate that particularly DSBs that occur in S‐phase but cannot use a non‐damaged sister chromatid as a repair donor, may heavily rely on TMEJ. These could be DSBs that occur in DNA segments that are not yet replicated, or DSBs induced at sites opposite a damaged sister chromatid (Lemmens et al , ). Also transposon mobilization, when co‐occurring at both sister chromatids, may be a physiological source of DSBs that completely rely on TMEJ for their repair (van Schendel et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that particularly DSBs that occur in S‐phase but cannot use a non‐damaged sister chromatid as a repair donor, may heavily rely on TMEJ. These could be DSBs that occur in DNA segments that are not yet replicated, or DSBs induced at sites opposite a damaged sister chromatid (Lemmens et al , ). Also transposon mobilization, when co‐occurring at both sister chromatids, may be a physiological source of DSBs that completely rely on TMEJ for their repair (van Schendel et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Pol θ and its related mutational signature are evolutionary conserved and were first described in Drosophila melanogaster, where Pol θ can repair DSBs induced by endonucleases or P element transposition (Chan et al , ). In the nematode Caenorhabditis elegans , Pol θ is required for the repair of replication stress‐associated DSBs that form at persistent replication‐blocking lesions and G‐quadruplex structures in DNA (Koole et al , ; Roerink et al , ; Lemmens et al , ; van Schendel et al , , ). Several lines of evidence have also implicated Pol θ in Alt‐EJ in mouse cells: TMEJ provides resistance to DNA strand breaking agents in bone marrow stromal cells (Yousefzadeh et al , ), TMEJ‐like footprints were observed at junctions of fused dysfunctional telomeres in embryonic fibroblasts (Mateos‐Gomez et al , ), and TMEJ was found to regulate the repair of exogenous DNA substrates (Yousefzadeh et al , ; Wyatt et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…A possible insight is provided by analysis of nematodes, where a single quadruplex has been shown to persist through multiple generations, arresting replication to create a 3′ end bordering a gap that is converted to a DSB during DNA replication (27). …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that epigenetic factors, DNA structures, and sequence motif influence the mutation rate (8,9,23,24). However, little is known about factors that influence the mutability of microsatellites.…”
Section: Mutability Of Microsatellitementioning
confidence: 99%
“…We considered replication timing, nuclear lamina binding region, G-quadruplexes, and predicted DNA shapes. Nuclear lamina binding regions are known to be associated with genomic fragile sites (23), while G-quadruplexes can cause replication errors (24). The impact of DNA shapes was not well known, but one DNA shape parameter (ORChID2) had been reported to be associated with mutation rate of somatic indels (9).…”
Section: Mutability Of Microsatellitementioning
confidence: 99%